KEBUDAYAAN DAN WISATA SEJARAH: EXSISTENSI OBYEK SEJARAH TERHADAP PERKEMBANGAN WISATA DI PARIANGAN KABUPATEN TANAH DATAR - Jamal Mirdad; Busatmin Bustamin; Desma Rustika A (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2020)
Indonesia is one of the countries that have the best tourist destinations in the world. This reality is supported by its natural wealth and various cultures. So that Indonesia is not only popular for its natural beauty but also for its historical tourist destinations. The crowning of Nagari Tuo Pariangan as the most beautiful village in the world by Travel Budget is proof of the existence of historical tourism in Indonesia. The purpose of this paper is to analyze Culture and Historical Tourism: The Existence of Historical Objects on Tourism Development in Pariagan, Tanah Datar Regency. This paper uses a qualitative descriptive approach, then analyzed using Creswell Analysis. The results showed that in Nagari Pariangan there are several historical tourism objects, but there are four popular objects including the long grave, Ishlah Mosque, Nasurek Stone, and Balai Saruang which greatly affect the existence of tourism development in Nagari Pariangan. On the policy side, the Regional Government supports the development of culture and history-based tourism, although not maximally.